Gambaran Perilaku Cyberbullying Pada Siswa Sekolah Menengah Atas - Reza, Reza Eka Ristanto; Indra Tri Astuti; Kurnia Wijayanti (STIKes Ibnu Sina Ajibarang, 2025)
Cyberbullying is increasingly becoming a problem among teenagers, especially with the advancement of technology and social media, which can have a negative impact on students' mental health. This study employs a descriptive quantitative method by conducting a survey of 168 high school students, selected using stratified random sampling techniques. Data were collected through a questionnaire that has been tested for validity and reliability. The results show that the average age of respondents is 16 years, with 56.5% of them being female. The most influential factor on cyberbullying behavior is peer influence (24.4%). Approximately 60.7% of respondents are involved in cyberbullying at a moderate level, and the most common type of behavior is harassment, where students send persistent disturbing messages. Several factors influencing this behavior include experiences of violence, peer influence, and social media usage.